Model Pengkuran Kinerja Lembaga Zakat di Indonesia (UIN Sunan Kudus, 2019)
Seeing the tasks of zakat institutions that are so complex, certainly indicates that the performance of zakat institutions need special attention to be evaluated in terms of management of zakat funds. Because zakat has a strategic role to assist the government in poverty alleviation programs and development programs. This study aims to explain the model of zakat institution performance measurement. The models described in this study consist of National Zakat Index (IZN), Zakat Village Index (IDZ), Center of Islamic Business and Economic Studies (CIBEST), Balance Scorecard, Indonesia Magnificence of Zakat (IMZ) and International Standard of Zakat Management (ISZM). The method used in this study is Library Research, and from the results of this study shows that each measurement model has the characteristics of each with different measurement methods with each other.